Demographic change and the rate of return in PAYG pension systems - Matthias Schön (Deutsche Bundesbank, 2020)
The currently observed demographic change consists of two independent develop-ments that differ in structure and persistence: (1) A slow, monotonic and (presum-ably) permanent ageing effect caused by an increasing life expectancy; (2) a morerapidly changing, non-monotonic and less permanent cohort effect caused by fluc-tuations in the size of cohorts. This paper shows the ageing effect has a positiveimpact on the rates of return households generate within pay-as-you-go (PAYG) pension system. The cohort effect, by contrast, results in winners and losers in PAYG systems. Taking Germany as an example and using a quantitative OLG model the paper shows that the two effects cause rate of return differentials withinthe pension system of almost 1.3 percentage points between generations.
Keywords: E27; E62; H55; J11; J26; 330; Demographic Change; Pension System; OLG Models